2021
DOI: 10.1186/s12879-021-06565-y
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus oralis MitraClip endocarditis following a dental procedure: a case report

Abstract: Background Transcatheter edge-to-edge mitral valve repair using the MitraClip device is increasingly used for high surgical risk patients with severe mitral regurgitation (MR). Previous guidelines for infective endocarditis prophylaxis prior to dental procedures focused on high-risk patients, but without explicit recommendation for MitraClip recipients. We believe this could be the first reported case to identify Streptococcus oralis as the causative organism. Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…5 Streptococcus oralis, an alpha-hemolytic streptococcus, is a member of the normal human oral microbiota, feasible of opportunistic pathogenicity. 6 Oral streptococcal infective endocarditis, can also result from not only invasive dental procedure but also daily dental activities. Therefore, oral hygiene, particularly in adult individuals with unclosed PDA, is extremely important and prophylactic antibiotics is needed when performing invasive dental procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Streptococcus oralis, an alpha-hemolytic streptococcus, is a member of the normal human oral microbiota, feasible of opportunistic pathogenicity. 6 Oral streptococcal infective endocarditis, can also result from not only invasive dental procedure but also daily dental activities. Therefore, oral hygiene, particularly in adult individuals with unclosed PDA, is extremely important and prophylactic antibiotics is needed when performing invasive dental procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study revealed that Streptococcus mutans are most frequent (47.9%) and Streptococcus oralis , detected in the present case, are found in 19.4% in patients with streptococcal infective endocarditis 5 . Streptococcus oralis , an alpha‐hemolytic streptococcus, is a member of the normal human oral microbiota, feasible of opportunistic pathogenicity 6 . Oral streptococcal infective endocarditis, can also result from not only invasive dental procedure but also daily dental activities.…”
Section: Discussionmentioning
confidence: 99%
“…Our search strategy included the use of the terms “infective endocarditis or infectious endocarditis” and “transcatheter mitral valve repair, percutaneous mitral valve repair, MitraClip, or PASCAL.” A manual search for these topics within case reports at major cardiology meetings was also performed until February 2023. A total of 23 publications describing 26 cases of IE following TEER treatment for severe MR were identified, 7–29 in addition to our one case. Our local ethics committee approved this case report and systematic review.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…S. aureus is the major causative microorganism (11/25 pts; 44%). However, infections of MitraClip caused by Enterococci (3/25 pts, 12%), Streptococci (2/25 pts, 8%) [ 6 , 32 ], Pseudomonas aeruginosa [ 33 ] or atypical microorganisms such as Bartonella haenselae [ 34 ] are also reported.…”
Section: Mitraclipmentioning
confidence: 99%